Revitalization of Ethical Leadership in Islamic Education: Principal's Strategy to Face the Challenges of Globalization in Madrasah - Novia, Atina; Siti Aimah (Managere: Indonesian Journal of Educational Management, 2024)
This research focuses on the role of ethical leadership in creating a positive school culture and facing challenges in the Islamic educational environment, especially in madrasas. This study aims to identify and analyze the leadership strategies used by school principals in applying ethical values as part of a leadership strategy to increase motivation, solve problems, and shape student character. The research method used is qualitative with a case study approach in MAN 2 Banyuwangi. Data were collected through in-depth interviews, participatory observations, and documentation with key informants consisting of principals, teachers, and quality control teams. The data analysis technique uses the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing validated by triangulation techniques. The results of the study show that school principals who apply ethical leadership through example, an inclusive approach in problem-solving, and the formation of a collaborative culture are able to create a harmonious school climate and support the development of students' character. The implications of this study highlight that ethical leadership plays an important role in facing the pressures of globalization and maintaining moral values in the Islamic educational environment. This research makes a practical contribution by providing guidance for school principals and other Islamic education leaders in implementing ethical leadership that not only focuses on academic achievement but also the formation of strong moral character among students.